Preparation and Characterization of Solid Electrolyte Doped With Carbon Nanotubes and its Preliminary Application in NO2 Gas Sensors - Luo, Rubai; Li, Qiqi; Du, Bin; Zhou, Shisheng; Chen, Yuheng (Frontiers in Materials, 2019)
In this work, a solid polymer electrolyte (SPE) doped with carbon nanotubes (CNTs) was used as a gas sensing material for a NO2 gas sensor. The electrolytes consisted of the ionic liquids (ILs) and CNTs, which were immobilized in a poly(vinylidene fluoride) (PVDF) matrix. The SPE membranes were characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), and cyclic voltammetry (CV). The experimental results show that the addition of an appropriate amount of CNTs can appropriately improve the electrochemical performance of the SPE membrane. It was shown that NO2 gas sensors with an appropriate amount of CNTs added to their SPEs had a higher gas sensitivity than those with SPE containing no CNTs. When the mass ratio of PVDF, N-methyl-2-pyrrolidone (NMP), IL, and CNT was 1:4:1:0.08, the SPE showed the best gas sensitivity, and its sensitivity is 0.00275 V/ppm.